Rehabilitation increases cortical activation during single-leg stance in patients with chronic ankle instability - Tengjia Ma; Chang Liu; Haozheng Li; Xiaoyun Xu; Yiran Wang; Weichu Tao; Xiao'ao Xue; Qianru Li; Rongshan Zhao; Yinghui Hua (Elsevier, 2024)
Background: Chronic ankle instability (CAI) has been considered a neurophysiological disease, having as symptoms dysfunction in somatosensory and motor system excitability. Rehabilitation has been considered an effective treatment for CAI. However, few studies have explored the effects of rehabilitation on neuroplasticity in the CAI population. Objective: The purpose of this study was to investigate the effects of rehabilitation on cortical activities for postural control in CAI patients and to find the correlation between the change in cortical activities and patient-reported outcomes (PROs). Methods: Thirteen participants with CAI (6 female, 7 male, age = 33.8 ± 7.7 years, BMI = 24.7 ± 4.9 kg/m2) received a home exercise program for about 40 min per day, four days per week and six weeks, including ankle range-of-motion exercise, muscle strengthening, and balance activities. Cortical activation, PROs and Y-balance test outcomes were assessed and compared before and after rehabilitation. Cortical activation was detected via Functional near-infrared spectroscopy (fNIRS) while the participants performed single-leg stance tasks. Results: The participants had better PROs and Y balance test outcomes after rehabilitation. Greater cortical activation was observed in the primary somatosensory cortex (S1, d = 0.66, p = 0.035), the superior temporal gyrus (STG, d = 1.06, p = 0.002) and the middle temporal gyrus (MTG, d = 0.66, p = 0.035) in CAI patients after rehabilitation. Moreover, significant positive correlations were observed between the recovery of ankle symptoms and the change of cortical activation in S1 (r = 0.74, p = 0.005) and STG (r = 0.72, p = 0.007) respectively. Conclusion: The current study reveals that six weeks of rehabilitation can cause greater cortical activation in S1, STG and MTG. This increase in cortical activation suggested a better ability to perceive somatosensory stimuli and may have a compensatory role in function improvement.